Legal protection for child criminals through diversion and restorative justice in the judicial system - Faturohman Faturohman (LEGAL BRIEF, 2025)
Legal protection for child criminals is a crucial issue in the Indonesian criminal justice system, given that children are viewed as individuals still developing and requiring a special approach. The application of diversion and restorative justice offers a solution to prevent children from experiencing formal justice processes that can potentially cause trauma and hinder their future. However, in practice, the implementation of both approaches still faces obstacles, such as a lack of understanding among law enforcement officials, a lack of supporting facilities, and suboptimal involvement of the community and victims in the recovery process. This study uses a normative juridical method with a legislative approach and conceptual analysis to assess the effectiveness of diversion and restorative justice as forms of legal protection for children. Data were obtained through a literature review of the Juvenile Criminal Justice System Law and various previous studies. The results show that diversion and restorative justice have been proven effective in reducing recidivism rates, restoring offender-victim relationships, and providing a more humane developmental environment for children. However, their effectiveness is highly dependent on the professionalism of law enforcement officials and the support of the social environment. In conclusion, the implementation of both approaches needs to be strengthened through increased law enforcement capacity, cross-institutional synergy, and public education